2007
DOI: 10.1111/j.1440-1754.2007.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and recurrence in treatment of phimosis using topical betamethasone in children in Hong Kong

Abstract: Topical steroid is an effective and safe treatment for phimosis, especially when combined with a good hygiene practice of the foreskin with daily cleansing and retraction. A trial of topical steroid treatment should be offered upon considering circumcision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
1
21
0
5
Order By: Relevance
“…Most commonly used and effective steroid for phimosis has been betamethasone dipropionate in concentrations ranging from 0.025 to 0.1% (5,6,8–20). Other steroids such as hydrocortisone (6), triamcinolone acetonide (21), clobetasol propionate (7,22,23), mometasone (24) and fluticasone propionate (25) have also shown good success rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly used and effective steroid for phimosis has been betamethasone dipropionate in concentrations ranging from 0.025 to 0.1% (5,6,8–20). Other steroids such as hydrocortisone (6), triamcinolone acetonide (21), clobetasol propionate (7,22,23), mometasone (24) and fluticasone propionate (25) have also shown good success rates.…”
Section: Discussionmentioning
confidence: 99%
“…Ku et al. (17) followed up patients for a mean of 2.45 years, and an actual physical examination was performed to give a reliable assessment of outcome. They reported a lower sustained success rate of 60.2% of the children.…”
Section: Discussionmentioning
confidence: 99%
“…In the series of WaiHung et al, there was significant difference on the first treatment outcome (four weeks) between boys <3 years (92.6%) and >3 years (70.4%) of age. 15 Orsola et al also reported 82% patients to have responded to the treatment within 4 weeks. 5 It appears that the response varies with the age group of the patient and decreases as the age of the patient increases.…”
Section: 7mentioning
confidence: 93%
“…13,14 The failure rate is much lower than Wai-Hung et al series results (14.8%). 15 Majority of patients (82.4%) responded within 4 weeks to topical steroid (0.05% betamethasone ointment). Significantly highest number of patients who responded within 4 weeks were <5 years old.…”
Section: 7mentioning
confidence: 99%
“…Várias drogas, classificadas como corticóides de alta, média e baixa potência, foram testadas, aplicadas duas vezes ao dia, por um período de quatro a oito semanas (Wright, 1994;Golubovic, Milanovic et al, 1996;Chu, Chen et al, 1999;Monsour, Rabinovitch et al, 1999;Lund, Wai et al, 2000;Orsola, Caffaratti et al, 2000;Elmore, Baker et al, 2002;Ashfield, Nickel et al, 2003;Ku, Chiu et al, 2007;Pileggi Fde e Vicente, 2007;Zampieri, Corroppolo et al, 2007;Esposito, Centonze et al, 2008;Palmer e Palmer, 2008). Em 1993, Jorgensen e Svensson, ao tratar balanite xerótica obliterante, com propionato de clobetasol tópico, a 0,05%, em cinqüenta e quatro crianças, obtiveram cura, em 70% dos casos.…”
Section: Introductionunclassified